CSTF2 supports hypoxia tolerance in hepatocellular carcinoma by enabling m6A modification evasion of PGK1 to enhance gycolysis - Zhang, Qiangnu; Zhang, Yusen; Fu, Chuli; He, Xiaoyan; Huang, Zuotian; Wu, Geyan; Wei, Teng; Jin, Wen; Yan, Lesen; Wu, Meilong; Peng, Gongze; Fan, LinLan; et al. (Cancer research, 2025)
Cleavage stimulation factor subunit 2 (CSTF2) is a fundamental factor in the regulation of 3′-end cleavage and alternative polyadenylation of pre-mRNAs. Previous work has identified a tumor-promoting role of CSTF2, suggesting that it may represent a potential therapeutic target. In this study, we aimed to elucidate the mechanistic function of CSTF2 in hepatocellular carcinoma (HCC). CSTF2 upregulation was frequent in HCC, and elevated levels of CSTF2 correlated with poor patient prognosis. Although CSTF2 inhibition did not suppress HCC growth under nonstress conditions, it supported tolerance and survival of HCC cells under hypoxic conditions. Mechanistically, CSTF2 increased phosphoglycerate kinase 1 (PGK1) protein production to enhance glycolysis, thereby sustaining the energy supply under hypoxic conditions. CSTF2 shortened the 3′ untranslated region of PGK1 pre-mRNA by binding near the proximal polyadenylation site. This shortening led to a loss of N6-methyladenosine (m6A) modification sites that are bound by YTH m6A RNA-binding protein F2 and increase degradation of PGK1 mRNA. Concurrently, hypoxia increased m6A modification of PGK1 mRNA near the proximal polyadenylation site that was recognized by the YTH m6A RNA-binding protein C1, which recruited CSTF2 to enhance the shortening of the PGK1 3′ untranslated region. A small-molecule screen identified masitinib as an inhibitor of CSTF2. Masitinib counteracted PGK1 upregulation by CSTF2 and suppressed the growth of HCC xenograft and patient-derived organoid models. In conclusion, this study revealed a function of CSTF2 in supporting HCC survival under hypoxia conditions through m6A modification evasion and metabolic reprogramming, indicating that inhibiting CSTF2 may overcome hypoxia tolerance in HCC.Significance: Targeting CSTF2 inhibits hepatocellular carcinoma survival in hypoxic microenvironments, which may be a promising therapeutic strategy for treating liver cancer.
Online veröffentlicht: 8. November 2024
Im Titel ist 6 bei m6A hochgestellt
Gesehen am 05.09.2025